Behavioral Determinants of Mating Success in Blackbuck under Semienclosed Condition: A Cross-Sectional Study in Shuklaphanta National Park, Nepal - Saud, Puja; Neupane, Juna; Chalise, Mukesh Kumar (International Journal of Zoology, 2022)
Knowing reproductive behavior is important for establishing a viable population of nationally endangered blackbuck in Nepal. This study explored the behavioral events and states associated with copulatory mountings in blackbuck by focal animal sampling method under semienclosed conditions of Hirapurphanta within Shuklaphanta National Park, Nepal. We recorded different behavioral initiations for the mating reproductive activities and the behaviors followed after copulatory mounting. Four dominant adult males were used as a subject. The highest number of copulatory mountings was observed during the months of February–March. Among the diurnal observational phases, the highest number of copulatory mountings was recorded during 9.00–12.00 hours followed by 15.00 hours onwards. Copulatory mounting was significantly preceded by sniffing the vulva of female and showing flehmen response, whereas copulatory mounting was followed by walking.